1983
DOI: 10.1007/bf00253546
|View full text |Cite
|
Sign up to set email alerts
|

67Ga-transferrin and 67Ga-lactoferrin binding to tumor cells: Specific versus nonspecific glycoprotein-cell interaction

Abstract: In order to evaluate the mechanisms which facilitate the transfer of 67Ga from transferrin in plasma to intracellular binding sites, lactoferrin, a glycoprotein with high affinity for 67Ga, was used as a probe to study the effect of protein binding on gallium uptake by tumor cells. The in vivo effect of transferrin and lactoferrin on the biodistribution of 67Ga was studied in nude mice bearing human malignant mesothelioma. Tumor uptake of 67Ga was reduced 30% by transferrin and 57% by lactoferrin compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…12) Vallabhajosula et al reported that the uptake of 67 Ga by tumors was reduced by Tf, as compared with 67 Ga-citrate alone, i.e., the uptake of 67 Ga by tumors occurred in an unbound form. 20) Kumagai et al reported that Tf receptors increased in hepatocytes during rat liver regeneration. 21) There is, however, no report concerning the involvement of Tf in the 67 Ga uptake by regenerating liver after partial hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…12) Vallabhajosula et al reported that the uptake of 67 Ga by tumors was reduced by Tf, as compared with 67 Ga-citrate alone, i.e., the uptake of 67 Ga by tumors occurred in an unbound form. 20) Kumagai et al reported that Tf receptors increased in hepatocytes during rat liver regeneration. 21) There is, however, no report concerning the involvement of Tf in the 67 Ga uptake by regenerating liver after partial hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…After overnight fasting blood was withdrawn and platelets were labeled with ["'Indium]tropolone (300-400 ,tCi) as we have previously described (9,10). 18-24 h later the pigs were sedated with a mixture of ketamine and xylazine (Ketalar, Rompun) given intramuscularly, then intubated and ventilated with a Harvard respirator and anesthetized intravenously with sodium pentobarbital (Fort Dodge Lab., Fort Dodge, IA) with the minimal effective dose as previously described (4).…”
Section: Methodsmentioning
confidence: 99%
“…Autologous platelets were labeled with ["'In]tropolone according to our previously described technique (9). Platelets deposited on the perfused substrate (X 106/cm2) were determined by gamma well counting of the perfused matrix and normalized by blood activity (counts), platelet counts in blood, and surface area (1)(2)(3)(4).…”
Section: Methodsmentioning
confidence: 99%
“…In the second step of the examination, regional cerebral blood volume (rCBV) was measured by scanning 12 hours later the patient in the same position under the tomograph but after a non saturating intravenous injection of 2 to 4 mCi of 68 GaC13 (25,26) just eluted from a generator (27,28). One ten minutes scan was taken ten minutes after injection to allow equilibrium of the tracer in the body.…”
Section: Measurement Of Rcbv and Rpsrmentioning
confidence: 99%